Promoting long term athlete development in cross country skiing through competency-based coach education: A qualitative study - Banack, H. R.; Bloom, G. A.; Falcao, W. R. (International Journal of Sports Science and Coaching, 2012)
Coach education programs in Canada and abroad have recently been framed around Long Term Athlete Development (LTAD), a seven-stage model that is based on the physical, mental, emotional, and cognitive development of children and adolescents. To date, limited empirical research on LTAD exists. The primary objective of this study was to identify whether individuals who completed a coach education course acquired an understanding of LTAD and whether they integrated this knowledge into their coaching practice. The secondary purpose was to identify information that could be used to improve the coach education program as well as the effectiveness of youth sport coaching in cross-country skiing. Results indicated the course was an effective technique for delivering the core principles of LTAD to coaches with little or no prior knowledge of the concept. As well, coaches successfully integrated the principles of LTAD into their coaching practices. These results are discussed in regard to improving the effectiveness of youth sport coaching.